Isolation and Characterization of Dillenia Fruit Mucilage: A Novel Polymer for Microspheric Delivery of Losartan Potassium - Chakraborty, Santanu; Khandai, Madhusmruti; Dhibar, Manami; Yadav, Shikha; Kumari, Honey (Drug Delivery Letters, 2020)
Objective: The present investigation was aimed to isolate, characterize and establish a natural polymer obtained from partially ripe and fresh fruits of Dillenia indica and its utility to deliver losartan potassium in a sustained manner from microspheric macromolecular dosage form. Methods: All the microspheres were prepared by ionotropic gelation technique and investigated for various physico-chemical parameters along with in-vitro drug release studies to optimize the concentration of algino-Dillenia polymeric blend required to develop twice daily sustained release dosage form of losartan potassium. Results: The functional characteristic studies and rheological behavior analysis suggested that extracted polysaccharide can be used as a viscosity modifying agent as well as sustain release ingredient. All the microsphere formulations exhibited excellent mucoadhesion properties and site-specific drug release. In-vitro studies revealed that the optimum concentration of algino-Dillenia polymeric blend is suitable to deliver losartan potassium in a sustained manner for a prolonged period of time. SEM study revealed that the microspheres were spherical in shape with a smooth outer surface having small cracks. XRD and DSC studies revealed that losartan potassium is present as an amorphous form in the prepared optimized microsphere formulation. Conclusion: Thus, the present studies demonstrated that Dillenia fruit mucilage has an interesting rheological behavior which may be used as a viscosity modifying agent and exhibit promising properties of a sustained release dosage form to deliver losartan potassium from its microspheric dosage form.
Keywords: microspheres